Calculation of the absorption coefficient of a weak electromagnetic wave by free carriers in quantum wires by using the Kubo-Mori method - Nguyen, Bau Quang; Dinh, Vuong Quoc; Nguyen, Lam Ba; Luu, Linh Bich (VNU Journal of Science: Mathematics - Physics; Vol 20 No 3AP, 2017)
Abstracts